THE CONSITUTIONAL OBLIGATION OF AN IDENTICAL TAX TREATMENT OF MARRIAGE, COMMON LAW PARTNERSHIPS AND SAME-SEX PARTNERSHIPS IN THE REPUBLIC OF SERBIA - Kostić, Svetislav V. (Pravni zapisi, 2022)
In this paper the author focuses on the question of the tax treatmentof same-sex partnerships in comparison to the treatment providedfor heterosexual marriages and common law partnerships (extramaritalunions) in the Serbian law. Namely, different treatment of certain socialphenomena can represent a prohibited form of discrimination only underthe condition that we show that the observed phenomena are comparable,precisely from the view point of the object of protection provided bythe prohibition of discrimination. The problem we face is that our understandingof certain phenomena has changed over time, as best illustratedby the fact that Aristotle, who introduced the concept of discrimination,would have found it difficult to understand the postulate that all peopleare equal in their rights and obligations before the law. The author startsfrom the premise that the tax treatment of same-sex partnerships shouldbe viewed through the perspective of the principle of equality in tax law,the principle contained in Article 91, para. 2 of the Serbian Constitution,which stipulates that the obligation to pay taxes and other duties shall begeneral and based on the economic power of taxpayers. Therefore, if asame-sex union contains the same aspects that affect the economic powerof taxpayers, aspects that exist in the case of heterosexual marriage andextramarital union, then the Serbian Constitution requires us to provideit with equal tax treatment resulting from living in a heterosexual partnership.In this way the author opens up the space for a critical review ofthe tax norms in the 2021 Draft Law on Same-Sex Partnerships, i.e. forproposing solutions that would enable easier, and above all more sustainablekey goal the law aspires to, which is to eliminate discrimination of thesame-sex partnerships in the Serbian legal system.
Keywords: same sex partnerships; discrimination; marriage; taxation; Constitution